A framework of the innovation system: a case of Thailand. (1st January 2014) - Iamratanakul, Supachart
The innovation systems aimed at increasing countries' competitive advantage and technological capabilities are less focused on developing countries. In addition, there remains a lack of research to determine whether innovation systems should explicitly exist for or be applied to individual countries or whether each country should change its system to integrate more innovative capabilities. In this paper, we explore the innovation systems in less successful developing countries, using Thailand as a case study, to characterise how the innovation system, specifically the national innovation system (NIS), applies and impacts Thailand as a whole and what the policy and theoretical implication should be for changing this system. An NIS, a set of distinct institutions which jointly and individually contribute to the development and diffusion of new technologies, is used as a tool for policy analysis and provides the framework for governments to form and implement policies to influence the innovation process.